(untitled) (Research, Society and Development, 2022)
This work had as main objective to identify and comparatively analyze the perception of student quality of a public federal university and a private university center. The instrument used addresses seven dimensions of functional quality concerning educational services: market reputation, security, administrative service, interpersonal relationships, infrastructure, educational aspects and academic aspects. 160 valid responses were obtained. The samples were characterized, the reliability of the study was verified, descriptive treatments were carried out by dimension and the final means by entity were identified. The administrative service and infrastructure dimensions obtained the highest and lowest averages, respectively, in the two institutions. There were complaints about the entities’ canteens and parking lots. It was found that the private HEI achieved numerically higher averages in all constructs of the instrument and the final average. However, in statistical treatment using the hypothesis test, it was concluded that the differences between the means are not significant. Finally, it was diagnosed a relevant theoretical contribution that may assist in the management of educational services related to the evaluated course. Another highlighted evidence is the need to expand scientific research on the theme of quality in Brazilian higher education.